The Implementation of Land Rights Relinquishment Policy for Green Open Spaces - Muslikan, Budi Arif; Lisdiyono, Edy (Unifikasi : Jurnal Ilmu Hukum, 2023)
The increased demand for decent housing at affordable prices has provided opportunities for housing development with government subsidies, also well-known as LIC/MBR housing. Low-Income Communities (LIC/MBR) are people who have limited purchasing power, so they need government support to buy housing. This study discusses the importance of land rights relinquishment for green open space so that developers are not only concerned with economic value but also social functions for a green, conducive, and flood-free environment. This study applied a normative juridical research method with analytical descriptive specifications and used secondary data as the main data. Developers’ obedience to providing green open space will have a positive impact, including the maintenance of the housing environment and the fulfillment of green open space in Demak Regency. Thus, by relinquishing the land rights, the green open space cannot be converted as it has been relinquished to the state.